Faktor yang berhubungan dengan perilaku konsumsi buah dan sayur siswa SMP di Denpasar - Rachman, Bella Nadya; Mustika, I Gede; Kusumawati, I. G. A Wita (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2017)
Background : Adolescence is the transition from child to adulthood. Adolescents usually change their lifestyle, includes consumption patterns, because it is influenced by peers’ environment. Adolescents nutritional needs are relatively large because of rapid growth and development process. One of the nutrition problems among adolescents is the lack of fruit and vegetable consumption that is influenced by internal and external factors.Objective : The purpose of this research was to know the relationship between attitude, nutrition knowledge, food preference, food availability, media exposure, and parents income with fruit and vegetable consumption behavior among SMPK 1 Harapan students. Methods : This study used cross sectional design and was conducted on April-May 2017. Subjects of this study were 85 grade VIII students selected by using simple random sampling. Information on attitude, nutrition knowledge, food preference, food availability, media exposure, and parents’ income were collected using questionnaire, while fruit and vegetables consumption behaviour were collected using semi quantitative food frequency questionnaire (SQ-FFQ).Results : The results of this study showed that most subjects has good fruit and vegetables consumption behavior (71.8%). There was a significant correlation between fruit and vegetables consumption behaviour with attitude (p<0,01), nutrition knowledge (p<0.01), food availability (p<0.01), media exposure (p<0.01), and parents income (p<0.01), but not related with food preference (p = 0.55).Conclusion :This study indicated a significant relationship between attitude, nutritional knowledge, food availability, media exposure, and parents income with fruits and vegetables consumption behaviour.